Nasopharyngeal carriage of Streptococcus pneumoniae, its associated factors, and antimicrobial susceptibility patterns among school children in Babile district, eastern Ethiopia - Fuad Abdi Mohammed; Rajesh Sarkar; Firayad Ayele; Kedir Urgesa (PLoS ONE, 2025)
Background Streptococcus pneumoniae colonization is a growing concern globally, including in Ethiopia. School-aged children are a key reservoir that can lead to endogenous infections and a potential source for the transmission in the community. However, little is known about its nasopharyngeal carriage rates in eastern Ethiopia. This study aimed to determine the nasopharyngeal carriage of Streptococcus pneumoniae , associated factors, and antimicrobial susceptibility patterns among primary school children in Babile District, Eastern Ethiopia. Methods A cross-sectional study was conducted at primary schools in the Babile district, Eastern Ethiopia, from November 15, 2022, to January 8, 2023. A systematic random sampling technique was used to enroll 337 schoolchildren. Data on sociodemographic and a potenail associated factors was collected using structured questionnaires. Nasopharyngeal swab samples were collected, transported in Amies medium, and cultured on blood and chocolate agar. Streptococcus pneumoniae was identified based on colony morphology, Gram staining, hemolysis, and biochemical tests. Antimicrobial susceptibility testing was performed using the Kirby-Bauer disk diffusion method. Data was entered in EpiData and analyzed in SPSS. Bivariate and multivariable logistic regression was used to identify factors associated with pneumococcal carriage, with statistical significance set at p < 0.05 and 95% CI. Results Overall nasopharyngeal carriage of Streptococcus pneumoniae was 16% (54/337) (95% CI: 12.0–20.0). The ages of the children ranged from 7 to 17 years, with a mean age of 12.75 years (SD ± 2.56). Passive smoking (AOR = 2.86, 95% CI: 1.45–5.67), single room house (AOR = 2.69, 95% CI: 1.32–5.49), greater than or equal to two siblings under 5 years old in the house(AOR = 4.8, 95% CI: 1.88–12.25), and previous respiratory tract infection (AOR = 3.24, 95% CI: 1.66–6.32) were significantly associated with nasopharyngeal carriage of Streptococcus pneumoniae. The isolated Streptococcus pneumoniae showed higher drug resistance to Tetracycline 23 (42.6%) and Trimethoprim-sulfamethoxazole (TMP-SMX) 18 (33.3%) and was found to be highly susceptible to oxacillin 32(72.2%), Vancomycin 41(75.9%) and Erythromycin 44 (81.48%). Conclusion A considerable proportion of asymptomatic nasopharyngeal carriage of Streptococcus pneumoniae in school children was associated with having a history of respiratory tract infection, being passive smokers, having greater than or equal to two siblings under 5 years old in the house, and living in a single-room house. A higher resistance of isolated Streptococcus pneumoniae was observed to tetracycline and trimethoprim-sulfamethoxazole. Thus, it is necessary to regularly assess the trend of antibiotic resistance andthe prevalence of pneumonia among asymptomatic children, and it is impretive to focus on modifiable associated factors in controlling the diseases.